2014
DOI: 10.1007/s10646-014-1288-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mercury exposure causes decreased escape takeoff flight performance and increased molt rate in European starlings (Sturnus vulgaris)

Abstract: Mercury is a widespread and persistent environmental contaminant that occurs in aquatic and terrestrial habitats. Recently, songbirds that forage from primarily terrestrial sources have shown evidence of bioaccumulation of mercury, but little research has assessed the effects of mercury on their health and fitness. There are many indications that mercury negatively affects neurological functioning, bioenergetics, and behavior through a variety of mechanisms and in a wide array of avian taxa. Effective flight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 54 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Methylmercury has been demonstrated to impair bird immune function (Hawley et al 2009, Lewis et al 2013), foraging behavior (Kobiela et al 2015), navigation (Moye et al 2016), and flight ability (Carlson et al 2014, Ma et al 2018, which could be particularly detrimental during long-distance migration. In this study, we used songbird feathers grown prior to autumn migration to examine the link between Hg exposure at breeding grounds and songbird survival until the subsequent spring return migration (a seasonal carry-over effect).…”
Section: Introductionmentioning
confidence: 99%
“…Methylmercury has been demonstrated to impair bird immune function (Hawley et al 2009, Lewis et al 2013), foraging behavior (Kobiela et al 2015), navigation (Moye et al 2016), and flight ability (Carlson et al 2014, Ma et al 2018, which could be particularly detrimental during long-distance migration. In this study, we used songbird feathers grown prior to autumn migration to examine the link between Hg exposure at breeding grounds and songbird survival until the subsequent spring return migration (a seasonal carry-over effect).…”
Section: Introductionmentioning
confidence: 99%
“…Additional impacts to flight endurance and refueling ability could result from effects of MeHg on the expression and function of other critical proteins like hormone-sensitive lipase, lipoprotein lipase, long chain acyl-CoA synthetase, albumin, malic enzyme, fatty acid synthase, and hemoglobin 9 , 23 , 63 , 73 , 75 . There is also the potential for mercury’s neurotoxicity to affect flight biomechanics, as observed in our birds 17 , which could further weaken endurance through reduced flight efficiency 9 , 17 , 76 . Much remains to be learned about the effects of MeHg on the physiological systems and processes that give migratory birds the remarkable ability to biannually fly thousands of kilometers between breeding and wintering grounds.…”
Section: Discussionmentioning
confidence: 91%
“…These values are below the threat level (Table ). It has been reported that the sublethal effects of Hg on the breeding success and flight efficiency of birds occur at 5-40 μg g −1 d.w. (Burger and Gochfeld, 1997;Carlson et al, 2014;Varian-Ramos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%